Polyphonic Legality: Power of Attorney Through Dialogic Interaction. (October 2019) - Harding, Rosie; Peel, Elizabeth
Building on Bakhtin's work on discourse, this article uses the concept of polyphony to explore capacity law praxis. Drawing on everyday interaction about power of attorney, we demonstrate how legal, lay and medical understandings of capacity operate dialogically, with each voice offering distinct expressions of legality. Analysing lay and medical interactions about Lasting Power of Attorney – the legal authority to make decisions on behalf of a person who loses the mental capacity to make their own decisions – we argue power of attorney holds a 'polyphonic legality'. We argue that legal concepts (like power of attorney) are constructed not solely through official law but through dialogic interaction in their discursive fields. We suggest 'polyphonic legality' offers an innovative approach to understanding how law works in everyday life, which is attentive to the rich texture of legality created by and through the multiple voices and domains of socio-legal regulation.